Intrinsic Elements in Memories Poem by Geoffrey Bache Smith (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Poetry is literary work that expresses a focused creative awareness of reality using words that have been chosen and arranged to elicit a particular emotional response by their meaning, sound, and rhythm. This article provides an analysis and aims to explore the intrinsic elements, which are symbol, imagery and figurative language presented in a poem by Geoffrey Bache Smith entitled Memories. The poem is about a soldier who missed his best friends in war and recalled the past memories with them. The method used for this study is descriptive qualitative method and used Kennedy (1995) intrinsic elements concept as the theory. Various sources such as undergraduate thesis, articles, books, and internet sources are used to provide further information. The final result demonstrates the intrinsic elements which are symbol, imagery and figurative language presented in a poem. It can be concluded that there are intrinsic elements in this poem, namely ten images consisting of nine visual images and one auditory imagery; two symbols; and two types of figurative language.